2011
DOI: 10.1007/s00384-011-1363-9
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind placebo-controlled trial to study therapeutic effects of probiotic Escherichia coli Nissle 1917 in subgroups of patients with irritable bowel syndrome

Abstract: PurposeTo study the therapeutic effects of probiotic Escherichia coli Nissle 1917 (EcN) in irritable bowel syndrome (IBS) and identify subgroups benefiting most.BackgroundSome trials investigating therapeutic effects in irritable bowel syndrome have shown benefits in IBS subgroups only. Probiotic treatment seems to be promising.MethodsPatients with irritable bowel syndrome (120; Rome II) were recruited to a prospective double-blind study and randomized to either EcN (n = 60) or placebo (n = 60) given for 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
102
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 28 publications
0
102
0
5
Order By: Relevance
“…Upon visual inspection of the data (ibid., see Figure 3 in Pineton de Chambrun et al 83 ), the effect occurred during weeks 6 to 8 with a sudden change in pain severity, mimicking a "recruitment bias" of unknown origin; however, it lacks any rational discussion and explanation. A similarly surprising and unexplained change occurred in the responder data of another study (ibid., see Figure 2 in Kruis et al), 92 during weeks 9 to 12, which may explain for the post-hoc significance in a subgroup of patients with post-infectious IBS. Finally, one study 108 found significant changes in bloating scores, but not for any other core symptoms of IBS.…”
Section: Global Outcomementioning
confidence: 86%
See 1 more Smart Citation
“…Upon visual inspection of the data (ibid., see Figure 3 in Pineton de Chambrun et al 83 ), the effect occurred during weeks 6 to 8 with a sudden change in pain severity, mimicking a "recruitment bias" of unknown origin; however, it lacks any rational discussion and explanation. A similarly surprising and unexplained change occurred in the responder data of another study (ibid., see Figure 2 in Kruis et al), 92 during weeks 9 to 12, which may explain for the post-hoc significance in a subgroup of patients with post-infectious IBS. Finally, one study 108 found significant changes in bloating scores, but not for any other core symptoms of IBS.…”
Section: Global Outcomementioning
confidence: 86%
“…86,87,96,97 again from different companies, in 2 instances combined with a prebiotic 86 or simethicone, 87 which makes direct comparison difficult. One study used a Streptococcus faecium strain 37 and 2 used different Escherichia coli strains, E. coli Nissle, 92 and E. coli.…”
mentioning
confidence: 99%
“…En ambos trabajos concluyeron que se observa una mejoría clínica significativa luego del consumo de probióticos, teniendo en cuenta el dolor abdominal y diarrea al comparar con el consumo de placebo (27)(28)(29)(30)(31)(32). La Tabla 1 resume los hallazgos de los estudios clínicos incluidos en los metaná-lisis previamente mencionados.…”
Section: Síndrome De Intestino Irritableunclassified
“…Only three published trials assessed ADEs related to probiotics in IBS in any systematic or standardized way. (27,29,34) A recent metaanalysis(39) showed a pooled relative risk (RR) for an adverse event of any type across all published trials of 1.21 (95% CI 1.02-1.44) and number needed to harm was 35. 16.5% of patients in all trials had an ADE on probiotics, compared with 13.8% of controls.…”
Section: Ibsmentioning
confidence: 99%
“…First, we constructed a dataset using all existing clinical trials that reported both efficacy and adverse drug events for both IBS (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) or IBD(40-49), as described in Figure 1 and Table 1. We sampled across the 95% confidence intervals for each trial weighted by the size of the trial (larger trials had a larger share of sampling).…”
mentioning
confidence: 99%